(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:1 Research objectives: -1. Preparing educational exercises according to the Driver model in learning some grips that are compatible with the capabilities of the research sample.2. Identifying the effect of instructional exercises according to Driver’s model in learning some grips.Research hypotheses: -1- The educational exercises, according to the Driver model, have a positive effect on some grips.1 _ 5 areas of research:1-5-1 The human field: a sample of the juniors of the Adhamiya Sports Club wrestling team.1-5-2 Time range: 1/30/2022 to 3/272022.1-5-3 Spatial field: Al-Adhamiya Sports Club hall in wrestling, Baghdad.The experimental method was used, and the research sample was selected from the wrestlers of the Adhamiya Sports Club, aged (12-14) years. The results produced by the tests proved the validity of the educational curriculum followed in the research, and its effectiveness in influencing learning the grips under study, and it was recommended to include exercises according to the driver’s model in the wrestling game as a training or educational method within the vocabulary of the training or educational unit.Keywords: educational exercises. Driver model. Learn the grips.